If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying S + -35 + 9 = 10 + -1s Reorder the terms: -35 + 9 + S = 10 + -1s Combine like terms: -35 + 9 = -26 -26 + S = 10 + -1s Solving -26 + S = 10 + -1s Solving for variable 'S'. Move all terms containing S to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + S = 10 + 26 + -1s Combine like terms: -26 + 26 = 0 0 + S = 10 + 26 + -1s S = 10 + 26 + -1s Combine like terms: 10 + 26 = 36 S = 36 + -1s Simplifying S = 36 + -1s
| -5(x+4)+x(x+4)=0 | | (5a+6b)-(3a-2b)= | | 4(y-5)=8 | | 12in+13in+x=180 | | 56=4w+12 | | 30=2u+16 | | 5w+11=46 | | 5w-11=74 | | 45-6x=9-10x | | 3d-19=d-1 | | 15+g=25 | | 10p+300=550 | | t+16=29 | | -5-5(t-2)= | | 4v-9=35 | | (x-24)+29+296=180 | | 5w+6-w=6w-2(w-3) | | 2x+(x+6)=-9 | | x^2+14x+193=0 | | 9-(5v+5)=-5v-4 | | 4(7x-1)+(7x-1)(7x-1)=0 | | x^2=306 | | (x+18)-27=14 | | (1/4)2.25-(1/16)+(1/2)2.25=(1/2)+2.25 | | x^2+14x+183=0 | | 14=6-2 | | 5=17 | | 4=13 | | -12c=48 | | 2(x+2)-4=12 | | 3x-9+4x=12 | | q-6=9 |